Disclosure of HIV status by people living with HIV/AIDS in tertiary care hospital in Western Maharashtra - Lathwal, Sumit; Mahajan, Saurabh; Yadav, Arun K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Disclosure is a planned and selective behavior that responds to the balance of potential risks and benefits of secrecy and disclosure of the person living with HIV. The disclosure of HIV status to sexual partners, family or friends, has been shown to be a potent stressor, as persons living with HIV/AIDS might fear negative reactions such as blame, rejection or violence. This study was carried out with an aim to study the patterns of HIV status disclosure and the problems related with it among the HIV positive patients admitted in a tertiary care hospital in Western Maharashtra. Methods: A cross-sectional descriptive, hospital based study carried out in a tertiary care hospital of Western Maharashtra from 01 October 2008 to 30 September 2010. A total of 92 consenting respondents admitted in the hospital were administered a pre tested semi-structured questionnaire to collect the data. The results were analysed using SPSS Ver 16.0. Results: Out of 74 married HIV positive individuals who had a chance to disclose their sero-status to spouse, 64 (86.5%, 95% CI-78.7% to 94.29%) voluntarily disclosed their HIV status to spouse while a small number i.e. 10 (13.5%, 95% CI- 05.71% to 21.29%) did not disclose their HIV status to spouse. Conclusions: This exploratory analysis suggests the need for tailoring interventions for improving disclosure decisions making and outcomes. Institutionalized measures need to be enforced judiciously to assist the HIV positive individuals to reveal their status to their wife and other members of their social group.